Strategic Pathways for the Olive Oil Chain in Argentina: Profitability, Sustainability and Oleo tourism - Winter, Patricia Lilian; Gennari, Alejandro Juan; Ciardullo, Vanina Fabiana; Santoni, Leonardo Javier (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The olive oil agri-food chain in Argentina is strategically relevant for rural development, employment, exports and tourism. Despite quality production and industrial capacity, the sector faces structural problems: high labour and energy costs, limited domestic consumption, and dependence on subsidized international competitors. This study analyses the chain using multicriteria programming across five dimensions: productive, economic-financial, commercial, environmental and tourism-territorial. The baseline was built from data collected between 2018 and 2024 (Agricultural Census 2018, official reports and international benchmarks), covering the country’s most representative producing regions (Catamarca, La Rioja, San Juan and Mendoza), which together account for over 90% of national output. Results from scenario simulations reveal trade-offs: export-oriented strategies maximize profit but increase vulnerability to global prices; internal consumption growth strengthens resilience yet moderates revenues; environmental sustainability improves efficiency through lower water use; and balanced development with olive oil tourism achieves robust outcomes across all dimensions. A novel contribution is the quantitative inclusion of tourism, showing its potential to generate rural employment and enhance brand value. The findings support forward-looking strategies that combine technological reconversion, market diversification, efficient resource use and tourism integration, offering policy guidelines for sustainable territorial development. Highlights: Multicriteria programming applied to the Argentine olive oil value chain. Integrated analysis of five dimensions: economic, productive, environmental, commercial, tourism. Scenarios reveal optimal strategies combining competitiveness and sustainability. Oleotourism emerges as a driver for regional value creation and diversification. Model supports bioeconomy-based policies for the olive oil sector’s future.